Increasing Tomato Yield in a Sandy Dryland Through the Application of UV Plastic Shade and Soil Amendment - Laila Safta; I Komang Damar Jaya; Herman Suheri; Sudirman Sudirman (Postgraduate, University of Mataram, 2025)
Cultivating tomato plants in dry, sandy soils aims to achieve high yields while enhancing or maintaining soil fertility. This study investigates the effects of soil amendments and ultraviolet (UV) plastic shade on tomato yield and various indicators of soil fertility. The experiment was conducted in the dryland of Gumantar village, North Lombok Regency, Indonesia, during the dry season from May to August 2024. The soil amendment factor included three levels: no soil amendment, chicken manure, and seaweed biochar. Meanwhile, the shading factor consisted of two levels: no shading and shading with UV plastic (200-micron thickness, which transmits 86% of UV light). All treatments received inorganic NPK fertilizer (16-16-16) at a rate of 1,200 kg per hectare. Treatments were arranged factorially using a randomized block design with three replications. Results showed an interaction between soil amendments and shading that affected soil pH, the number of fruits, and fruit weight per plant and plot. The highest fruit weight per plant, recorded at 4.2 kg with 100.7 fruits, was achieved using seaweed biochar and shading. The treatments slightly improved soil fertility indicators, such as soil organic carbon (C-organic), total microbial count, and cation exchange capacity. Applying soil amendment and UV plastic shading can be a sustainable practice for tomato crops production in sandy dryland soils